DISEASE CONTROL PURPLE BLOTCH (Alternaria porri L.) USING a PESTICIDEPLANT EXTRACT of BETEL LEAF ON the ONION PLANT (Allium ceppa L.) - Novia Mokalu; James B. Kaligis (Sam Ratulangi University, 2021)
Red onion is one of the vegetables that have important meaning for the people of the economic value and nutritional content. Onions contain calories, carbohydrates, fat, protein, dietary fiber, vitamins, and minerals. Red onion also contains the compound allicin and essential oils are bactericidal and fungicidal against bacteria and fungi. Demand for onion is good for consumption or seedlings in the country has increased. Every year almost always an increase in the production of red onion, but it has not been able to offset the increase in demand onion nationally along with the increasing population and the development of the processing industry. Keywords: red onion; betel leaf; extract. Abstrak Bawang merah merupakan salah satu komoditas sayuran yang mempunyai arti penting bagi masyarakat baik dari nilai ekonomisnya maupun kandungan gizinya. Bawang merah mengandung kalori, karbohidrat, lemak, protein, serat makanan, vitamin, dan mineral. Bawang merah mengandung senyawa allicin dan minyak atsiri yang bersifat bakterisida dan fungisida terhadap bakteri dan jamur. Permintaan akan bawang merah baik untuk konsumsi ataupun bibit dalam negeri mengalami peningkatan. Setiap tahun hampir selalu terjadi peningkatan produksi bawang merah, akan tetapi hal tersebut belum mampu mengimbangi peningkatan permintaan bawang merah secara nasional seiring dengan bertambahnya jumlah penduduk dan berkembangnya industri olahan. Kata kunci: bawang merah; daun sirih; ekstrak.